Metaverse Technology Research in Tourism and Hospitality Marketing in Indonesian Context: A Systematic Review - Mmari, Prosper Wilson; Sumarwan, Antonius (Indonesian Journal of Tourism and Leisure, 2024)
This article urgently examines the pressing need for research on metaverse technology (MT) within the tourism and hospitality marketing (THMK) context in Indonesia. Despite its potential, the current state-of-art-of MT research in THMK remains underexplored and limited particularly within tourism and hospitality marketing landscape. Through a systematic literature review (SLR) using the PRISMA Protocol and focusing on ProQuest database articles from 2012-2022, this study vigorously assessed 313 articles narrowing down to 34 relevant ones. These articles were meticulously analyzed to unveil the current state of MT within THMK context for the past decade. The study findings revealed that the current state of art of MT Research in THMK is substantially increasing although there were relatively limited studies in hospitality setting with very narrow and limited range of theoretical and methodical perspectives. Six dimensions of MT in THMK were identified, namely big data analytics, 3-D virtual representation, and augmented reality (AR), virtual reality (VR), smart, Internet of Things and blockchain technology. Using SLR provides an empirical foundation for understanding the current landscape of MT research in THMK within Indonesia, highlighting the need for further exploration and development. By addressing this urgent research gap, scholars and practitioners can unlock the full potential of MT in transforming THMK practices in Indonesia.